The Fostering Student Learning Independence in Physical Education Learning Based on Gender: Integrating Teaching Styles - Pebriyandi, Pebriyandi; Mashud, Mashud; Warni, Herita (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aimed to increase students' learning independence in physical education by integrating two teaching styles, namely practice style and inclusion, in students of SD Alam Muhammadiyah Martapura. Materials and methods. This study used a pre-experiment research design with one group pre-post test design. The study sample consisted of 30 students, 14 girls and 16 boys. The research methodology included three phases: pre-test, treatment, and post-test. In the pre-test phase, students carried out a learning independence test using conventional teaching styles. Next, students were treated with the integration of practice style and inclusion teaching style for 4 weeks. A post-test was then conducted to see changes in learning independence after the treatment. Results. The results showed that the mean pretest score was 63.23 ± 7.71 while the posttest score was 71.50 ± 5.63. Statistical analysis using One Way Anova shows that there is a significant difference in learning independence between male and female students. Responsibility and initiative factors were also analysed, showing that female students were dominant in the responsibility factor of not depending on others, while both males and females were equally positive in the responsibility factor of following instructions well and earnestly. Conclusion. The conclusion of this study is that the integration of practice style teaching with inclusion is effective in increasing students' learning independence. These results provide strategic implications for teachers in developing differentiated and inclusive learning methods to improve students' learning independence soft skills.